2021
DOI: 10.3390/ijms22094446
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor: A Multifaceted Actor in Breast Cancer

Abstract: Breast cancer (BC) is one of the most common cancers in women worldwide. Even though the role of estrogen receptor alpha (ERα) is extensively documented in the development of breast tumors, other members of the nuclear receptor family have emerged as important players. Synthetic glucocorticoids (GCs) such as dexamethasone (dex) are commonly used in BC for their antiemetic, anti-inflammatory, as well as energy and appetite stimulating properties, and to manage the side effects of chemotherapy. However, dex trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 153 publications
0
43
0
1
Order By: Relevance
“…For example, in ovarian and endometrial cancer cells, increased GR expression has been associated with poor prognoses [83,84]. GR expression is also correlated with a poor prognosis in estrogen receptor alpha (ERα)-negative breast cancer; however, it is correlated with a good prognosis in ERα-positive breast cancer [85]. An increase in stress-driven GCs has been associated with breast cancer progression [85,86].…”
Section: Glucocorticoids and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in ovarian and endometrial cancer cells, increased GR expression has been associated with poor prognoses [83,84]. GR expression is also correlated with a poor prognosis in estrogen receptor alpha (ERα)-negative breast cancer; however, it is correlated with a good prognosis in ERα-positive breast cancer [85]. An increase in stress-driven GCs has been associated with breast cancer progression [85,86].…”
Section: Glucocorticoids and Cancermentioning
confidence: 99%
“…GR expression is also correlated with a poor prognosis in estrogen receptor alpha (ERα)-negative breast cancer; however, it is correlated with a good prognosis in ERα-positive breast cancer [85]. An increase in stress-driven GCs has been associated with breast cancer progression [85,86]. In contrast, an in vitro study using cancerous epithelial prostrate cells observed a favorable prognosis for non-small cell lung cancers expressing GR, suggesting that GR may function as a tumor suppressor in these contexts [87,88].…”
Section: Glucocorticoids and Cancermentioning
confidence: 99%
“…Clinically, synthetic glucocorticoids (GR agonists) such as dexamethasone are ubiquitously used in breast cancer in conjunction with chemotherapy to mitigate hypersensitivity reactions, and for their antiemetic, anti-inflammatory, as well as orexigenic properties. However, dexamethasone triggers different effects depending on the breast cancer subtype [ 149 ].…”
Section: Glucocorticoid Receptor Signallingmentioning
confidence: 99%
“…[3]. Кроме того, в зависимости от подтипа РМЖ, GC могут значительно способствовать прогрессированию опухоли [2,4].…”
Section: Introductionunclassified